2016
DOI: 10.1371/journal.pone.0168054
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Vehicles: Disengagements, Accidents and Reaction Times

Abstract: Autonomous vehicles are being viewed with scepticism in their ability to improve safety and the driving experience. A critical issue with automated driving at this stage of its development is that it is not yet reliable and safe. When automated driving fails, or is limited, the autonomous mode disengages and the drivers are expected to resume manual driving. For this transition to occur safely, it is imperative that drivers react in an appropriate and timely manner. Recent data released from the California tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(166 citation statements)
references
References 8 publications
2
146
0
3
Order By: Relevance
“…Markvollrath, Schleicher, and Gelau (2011) reported delayed reactions (i.e. speed reduction) for ACC users when approaching curves or entering fog, while Dixit, Chand, and Nair (2016) showed that reaction times in taking control of the vehicle after disengagement of the autonomous mode increases with vehicle miles travelled. Xiong, Boyle, Moeckli, Dow, and Brown (2012) showed that drivers' adaptive behaviorand therefore the safety implications of ACC-is related to trust in automation, driving styles, understanding of system operations and the driver's personality.…”
Section: Literature Resultsmentioning
confidence: 99%
“…Markvollrath, Schleicher, and Gelau (2011) reported delayed reactions (i.e. speed reduction) for ACC users when approaching curves or entering fog, while Dixit, Chand, and Nair (2016) showed that reaction times in taking control of the vehicle after disengagement of the autonomous mode increases with vehicle miles travelled. Xiong, Boyle, Moeckli, Dow, and Brown (2012) showed that drivers' adaptive behaviorand therefore the safety implications of ACC-is related to trust in automation, driving styles, understanding of system operations and the driver's personality.…”
Section: Literature Resultsmentioning
confidence: 99%
“…Recent research suggested that current levels of technology from frontrunners like Google and Mercedes-Benz still experience malfunctions that require the need for human intervention [16]. Further issues arise with regard to the amount of miles the cars will need to be tested for in order to obtain statistically relevant data to demonstrate the vehicles' safety.…”
Section: Journal Of Advanced Transportationmentioning
confidence: 99%
“…Rau et al [17] developed a method to identify crashes, which could be addressed by AV technology, by mapping automated vehicle functions to five layers of crash information (location, precrash scenario, driving conditions, travel speed, and driver condition). Real-world data from AV testing in California has increasingly been utilised in recent research [16,[18][19][20]. For example, Schoettle and Sivak [18] found that AVs were not at fault in any crashes and the overall injury severity was lower for crashes involving AVs than for crashes involving human-driven vehicles (HVs).…”
Section: Journal Of Advanced Transportationmentioning
confidence: 99%
“…The convenient calculations still deviate greatly from reality. Second, previous research on vehicles' characteristics has concentrated on steady steering [53][54][55][56]. However, lane changes and overtaking by heavy trucks on highways, as a frequent driving behavior, could gain more attention in the near future.…”
Section: And Wu Investigated Lyapunov Concept Exponents and Applicatimentioning
confidence: 99%